Sacred Nature: Earth-based Spirituality as Popular Religion in the Pacific Northwest - Shibley, Mark A. (Journal for the study of religion, nature and culture, 2011)
There is a range of earth-based spirituality in the Paci?c Northwest of the United States that collectively amounts to Nature Religion—a popular religiosity that makes nature sacred. The mythic, experiential, ritualistic, and communal dimensions of this folk religion—expressed in regional literature, rituals of leisure, and the environmental movement—has come to have wide currency in public life. An understanding of this nature religion has broad implications for the study of American politics and religious diversity.